Revision of the Index of General Business Conditions - Frickey, Edwin (The Review of Economics and Statistics, 1932)
chart and its predecessors, and the relations among the curves and their significance are comparable with those found in the study of similar index charts extending back to I875. Such changes as have been made in the present revision are directed toward improvement in the accuracy and clarity of the picture given by the three curves. These changes, like those in earlier revisions, have been intended, not to abandon in whole or in part, but to reinforce, the fundamental principle of the chart.'